THE RELATIONSHIP BETWEEN PRODUCTION OF PROTEIN A, CAPSULE STRUCTURE AND SOME ENZYMES OF STAPHYLOCOCCUS AUREUS ISOLATED FROM INFECTIONS OF HUMAN AND ANIMALS - AL-Taan, Safana, A. S.; Al-Jobori, ASMAA, H. (The Iraqi Journal of Veterinary Medicine, 2021)
Thirty-five isolates of Staphylococcus were isolated out of 100 clinical specimens were collected from different infections of human and animals. These isolates were identified as Staphylococcus aureus, 15 of them isolated from human, 15 from cows and only 5 isolates from poultry. Twenty-five (71.4%) isolates of different sources revealed positive results for the detection of protein A, capsule formation and enzyme production of phosphatase, DNase and haemolysin. Seven (20 %) isolates showed negative results for both protein A and capsule as well as for the production of enzymes while only three (8.5%) isolates were not capsulated but able to produce protein A and the enzymes. During the detection of protein A, capsule structure and production of some enzymes, we found that the best value of pH used was the range of 7-7.5. The present study indicated that the presence of protein A and capsule structure is highly associated with the virulence of isolates, and loss of protein A doesn’t necessary mean loss of capsule as well. The ability of the isolates to produce their essential enzymes to induct the infection is highly correlated with the ability to produce protein A, without considering the source of the isolates.